2013
DOI: 10.1002/ange.201301676
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Chiral Oxathiozinone Scaffolds: Efficient Synthesis of Hindered Enantiopure Sulfinamides and Sulfinyl Ketimines

Abstract: Ist das S‐O? Die im Titel bezeichneten Molekülgerüste verfügen über eine hoch aktive und ausreichend differenzierte S‐O‐Bindung für die effiziente Synthese enantiomerenreiner Sulfinamide. Die beschriebene Methode ist praktisch und umweltverträglich und könnte als Grundlage für ein ökonomisches kommerzielles Verfahren zur Herstellung sperriger Sulfinamide dienen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…[29] In 2013 Han et al developed a new methodology to access highly sterically hindered sulfinylketimines. [30] They compared the effect of the substituent on the sulfinyl group and have shown that 2,4,6-triisopropylphenyl gave the best diastereoselectivity in the reduction reaction (Scheme 22).…”
Section: Eurjocmentioning
confidence: 99%
“…[29] In 2013 Han et al developed a new methodology to access highly sterically hindered sulfinylketimines. [30] They compared the effect of the substituent on the sulfinyl group and have shown that 2,4,6-triisopropylphenyl gave the best diastereoselectivity in the reduction reaction (Scheme 22).…”
Section: Eurjocmentioning
confidence: 99%
“…Up to now, chiral sulfinamides were mainly obtained by the nucleophilic substitution reaction between amines and chiral auxiliary agents containing sulfoxide groups (S=O) and leaving groups such as mercapto 11,12 and alkoxy. [13][14][15] Of course, the amount of chiral auxiliaries was equivalent or even excessive in this strategy; what is more, the amines were required to have strong nucleophilicity and the chiral adjuvant needed to have sufficient steric hindrance. In addition to poor atom economy and harsh reaction conditions, this strategy also reflected the lack of universality of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to poor atom economy and harsh reaction conditions, this strategy also reflected the lack of universality of the substrate. [11][12][13][14][15] Therefore, it is of great significance to develop asymmetric catalytic methods with high atom economy to prepare chiral sulfenamides that are difficult to obtain by traditional methods (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations